[Bmim]2SbCl5: a main group metal-containing ionic liquid exhibiting tunable photoluminescence and white-light emission. Issue 15 (19th January 2015) - Wang, Ze-Ping; Wang, Jin-Yun; Li, Jian-Rong; Feng, Mei-Ling; Zou, Guo-Dong; Huang, Xiao-Ying
Abstract : Presented is an antimony-based photoluminescent material, namely [Bmim]2 SbCl5, exhibiting bright yellow and white light photoluminescence with quantum yield as high as 86.3%. Abstract : An antimony-based photoluminescent ionic liquid, namely [Bmim]2 SbCl5, has been synthesized and characterized. It exhibits bright yellow and white light emission, with quantum yield as high as 86.3% under UV irradiation.